Manajemen Risiko Teknologi Informasi Menggunakan Framework ISO 31000:2009 Studi Kasus : Pembobolan ATM BCA Tahun 2010 - Tampubolon, Anthon; ., Suhardi (Yayasan Petra Harapan Bangsa, 2011)
Information Technology has succeeded change the paradigm of customer in the transaction. The transactions are beginning by coming to the bank teller, but now they can easily using a mobile phone, internet or ATM outlets that distributed in various strategic places by using an ATM card. In addition to facilitate customers in the transaction, Information Technology has also become a competitive advantage for banks to attract retail customers. However Advancement of Information Technology is closely linked to the risk that must be faced by the customers and the bank. In order to optimize the target of Information Technology, a company must implement an integrated risk management in corporate management (ERM). This paper presents a related case study of information technology issue that occur in company in the retail banking sector, the analysis performed using the ISO 31000:2009 framework. Framework considers the risk of Information Technology as an integrated part of the enterprise risk framework. This study uses secondary data from annual reports and company websites for research.